(untitled) (Revista Peruana de Investigación Educativa, 2016)
The objective of this study is twofold. First, to describe how teachers’ and schools’ characteristics are associated with teacher absenteeism. Second, to explore the relationship between teacher absenteeism and student achievement (mathematics and language), after holding constant student, school and contextual variables. The study uses the Young Lives’ School Survey database which has information for urban and rural schools in Peru in order to answer these two objectives. Using multivariate regression models (nonlinear), we identify what teacher variables are associated with teacher absenteeism. Then, we use propensity score matching to estimate the relationship between teacher absenteeism and student achievement in math and reading comprehension. Our main findings are that one of the key predictors for teacher absenteeism is the school principal’s attendance; in other words, teachers whose school principal was absent during the last month previous to the survey are four times more likely to be absent than peers whose school principal was not absent. Finally, we found that teacher absenteeism is negatively associated with student achievement (at least in math) after holding constant child, family, teacher, school and contextual variables.